=3y-11, 4x-3y=-26 Substitution
Answer: x2= 6
FYI: The x2 is x squared
Step-by-step explanation:
Simplifying
4x2 + 7 = 31
Reorder the terms:
7 + 4x2 = 31
Solving
7 + 4x2 = 31
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-7' to each side of the equation.
7 + -7 + 4x2 = 31 + -7
Combine like terms: 7 + -7 = 0
0 + 4x2 = 31 + -7
4x2 = 31 + -7
Combine like terms: 31 + -7 = 24
4x2 = 24
Divide each side by '4'.
x2 = 6
Simplifying
x2 = 6
Answer:9+2<17
Step-by-step explanation: